Prophylactic Vancomycin Drops Reduce the Severity of Early Bacterial Keratitis in Keratoprosthesis. - Aris Konstantopoulos; Xiao Wei Tan; Gwendoline Tze Wei Goh; Padmanabhan Saraswathi; Liyan Chen; Chan Lwin Nyein; Lei Zhou; Roger Beuerman; Donald Tiang Hwee Tan; Jod S Mehta (PLoS ONE)
Background Artificial cornea transplantation, keratoprosthesis, improves vision for patients at high risk of failure with human cadaveric cornea. However, post-operative infection can cause visual loss and implant extrusion in 3.2-17% of eyes. Long-term vancomycin drops are recommended following keratoprosthesis to prevent bacterial keratitis. Evidence, though, in support of this practice is poor. We investigated whether prophylactic vancomycin drops prevented bacterial keratitis in an animal keratoprosthesis model. Methodology Twenty-three rabbits were assigned either to a prophylactic group (n = 13) that received vancomycin 1.4% drops 5 times/day from keratoprosthesis implantation to sacrifice, or a non-prophylactic group (n = 10) that received no drops. All rabbits had Staphylococcus aureus inoculation into the cornea at 7-12 days post-implantation and were sacrificed at predetermined time-points. Prophylactic and non-prophylactic groups were compared with slit-lamp photography (SLP), anterior segment optical coherence tomography (AS-OCT), and histology, immunohistochemistry and bacterial quantification of excised corneas. Corneal vancomycin pharmacokinetics were studied in 8 additional rabbits. Results On day 1 post-inoculation, the median SLP score and mean±SEM AS-OCT corneal thickness (CT) were greater in the non-prophylactic than the prophylactic group (11 vs. 1, p = 0.049 and 486.9±61.2 vs. 327.4±37.1 μm, p = 0.029 respectively). On days 2 and 4, SLP scores and CT were not significantly different. Immunohistochemistry showed a greater CD11b+ve/non-CD11b+ve cell ratio in the non-prophylactic group (1.45 vs. 0.71) on day 2. Bacterial counts were not significantly different between the two groups. Corneal vancomycin concentration (2.835±0.383 μg/ml) exceeded minimum inhibitory concentration (MIC) for Staphylococcus aureus only after 16 days of vancomycin drops. Two of 3 rabbits still developed infection despite bacterial inoculation after 16 days of prophylactic drops. Conclusions Prophylactic vancomycin drops provided short-term benefit, but did not prevent infection. Achieving MIC in the cornea was not sufficient to prevent Staphylococcus aureus keratitis. Patients should continue to be counselled regarding the risk of infection following keratoprosthesis.